2018
DOI: 10.1007/s00125-018-4767-z
|View full text |Cite
|
Sign up to set email alerts
|

Afternoon exercise is more efficacious than morning exercise at improving blood glucose levels in individuals with type 2 diabetes: a randomised crossover trial

Abstract: Aims/hypothesisExercise is recommended for the treatment and prevention of type 2 diabetes. However, the most effective time of day to achieve beneficial effects on health remains unknown. We aimed to determine whether exercise training at two distinct times of day would have differing effects on 24 h blood glucose levels in men with type 2 diabetes.MethodsEleven men with type 2 diabetes underwent a randomised crossover trial. Inclusion criteria were 45–68 years of age and BMI between 23 and 33 kg/m2. Exclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
194
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(211 citation statements)
references
References 10 publications
(15 reference statements)
11
194
4
2
Order By: Relevance
“…Exercise increases the concentration of GLUT-4 in the cell membrane and increases glucose uptake in skeletal muscles [22][23][24]. Acute exercise increases glucose tolerance and insulin sensitivity and blood glucose reduction within 20-72 h, depending on the exercise intensity, form, duration, and observation time [25][26][27][28][29][30][31][32][33]. Studies have shown that acute moderate-intensity endurance training leads to a reduction in blood glucose levels [25,30], whereas light and short resistance and endurance training shows no effect [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Exercise increases the concentration of GLUT-4 in the cell membrane and increases glucose uptake in skeletal muscles [22][23][24]. Acute exercise increases glucose tolerance and insulin sensitivity and blood glucose reduction within 20-72 h, depending on the exercise intensity, form, duration, and observation time [25][26][27][28][29][30][31][32][33]. Studies have shown that acute moderate-intensity endurance training leads to a reduction in blood glucose levels [25,30], whereas light and short resistance and endurance training shows no effect [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Beneficial effects of time-restricted feeding for weight loss and metabolic improvement have been recently established in rodents, 194,195 followed by emerging translational studies in humans. 203,204 Understanding the function of the human circadian timing system has a tremendous application in chronopharmacology. 202 Furthermore, recent evidence suggests that timed exercise has the potential to improve metabolic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…202 Furthermore, recent evidence suggests that timed exercise has the potential to improve metabolic characteristics. 203,204 Understanding the function of the human circadian timing system has a tremendous application in chronopharmacology. 205 Indeed, liver clocks have important impact on the response to numerous medications, which should certainly be F I G U R E 3 Clock in the dish: approaches for molecular in-vitro studies of human peripheral oscillators.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should also examine potential biological benefits of performing PA at certain times of the day. For example, there are mixed findings about the time of day at which PA may optimally influence blood sugar control .…”
Section: Discussionmentioning
confidence: 99%